Route of Mannheimia haemolytica and Pasteurella multocida Vaccine Administration Does Not Affect Health or Performance of Receiving Heifers - T. Spore; M. E. Corrigan; T. R. Parks; C. S. Weibert; M. L. DeTray; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
Light weight stocker calves often experience health problems shortly after arrival to feeding facilities. Preventative health programs are routinely administered to calves upon arrival to reduce the incidence of Bovine Respiratory Disease. The major route of vaccine administration in cattle is via injection through either intramuscular or subcutaneous routes. Several products have been introduced that utilize the intranasal route of vaccine administration. There are several reasons why intranasal vaccine administration may be more beneficial: 1) Intranasal vaccine administration alleviates concerns that injections pose for Beef Quality Assurance programs. 2) Intranasal vaccine administration may be less stressful on the animal. 3) Intranasal vaccine administration delivers the vaccine to the site of infection in the case of respiratory pathogens, and may provide a different adaptive immune response to the vaccine. The objective of this study was to determine the effects of route of administration of theMannheimia haemolyticaandPasteurella multocidafractions of the vaccine regimen on receiving cattle growth performance, health, and mortality.
Keywords: intranasal vaccine; health; stocker